Analysis of Export Competitiveness of Indonesian Cocoa Beans in the International Market - Wulandari, Wisnu Arum; Widjojoko, Tatang (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4436, 2021)
Cocoa is one of the plantation commodities that has an important role in economic activity in Indonesia. Cocoa is also one of Indonesia's export commodities which is quite important as a source of foreign exchange. This study aims to compare the competitiveness of Indonesian cocoa exports with major exporting countries of world cocoa beans such as Ivory Coast, Ghana, Nigeria and Cameroon from 2009 to 2018. The comparable cocoa commodity is cocoa beans. This study uses descriptive analysis with the Revelaved Comparative Advantage (RCA) approach and the Trade Specialization Index (TSI). Revelaved Comparative Advantage analysis is used to determine the level of competitiveness of Indonesian cocoa beans, Ivory Coast, Ghana, Nigeria and Cameroon, while ISP is used to determine Indonesia's position as an exporter or importer of cocoa beans. RCA analysis shows that Indonesian cocoa commodities have a comparative advantage in the international market in the 2009-2018 period, while ISP analysis shows that in the 2009-2018 period Indonesia tended to be a cocoa bean exporter country